Non-invasive electromagnetic wave sensor for flow measurement and biphase application / Oon Cheen Sean - Oon , Cheen Sean (2017)
Multiphase flow measurement is important in chemical processing, water treatment and oil & gas industry. The multiphase flow sensor proposed in this research utilizes the resonant frequencies that occur inside a cavity and the differences in the permittivity of the measures phases. By measuring this response over the range of discrete frequencies the sample can be characterised. Polar material like water has relatively high permittivity (er = 81), while non-polar material such as oil and gas have low permittivity value (er = 2.2-2.5) and (er = 1) respectively. Hence, a small change in the water fraction may result in a comparatively large frequency shift. In this research, the electromagnetic cylindrical cavity sensor system successfully demonstrated its capability to analyze various fractions of water-gas mixture. The results were consistent in the case of both the static and dynamic flow. The statistical analysis of the captured data showed a linear relationship of the amplitude data with the change in the water fractions. It was also found that the technique was independent of the temperature change. The system was able to successfully detect the stratified, wavy, elongated bubbles and homogeneous flow regimes. The electromagnetic rectangular cavity sensor system is introduced to pick up the tiny shifts in the permittivity when the low permittivity material is used or temperature changes. The microwave sensor system is able to detect water-air fraction, water-oil fraction, oil-air fraction and water temperature. The novel solution of the combination of both cylindrical and rectangular sensor system demonstrates the ability to detect both high and low permittivity changes. These dual-cavity sensor cavity systems have been able to detect water level, flow regime and temperature in the pipe. It also demonstrates that microwave sensors based on the principle of changing permittivity can replace conventional measurement techniques.